NGF-TrkA Signaling by Sensory Nerves Coordinates the Vascularization and Ossification of Developing Endochondral Bone - Tomlinson, R; Li, Z; Zhang, Q; Goh, B; Li, Z; Thorek, D; Rajbhandari, L; Brushart, T; Minichiello, L; Zhou, F; Venkatesan, A; Clemens, T (Cell Press, 2016)
Developing tissues dictate the amount and type of innervation they require by secreting neurotrophins, which promote neuronal survival by activating distinct tyrosine kinase receptors. Here, we show that nerve growth factor (NGF) signaling through neurotrophic tyrosine kinase receptor type 1 (TrkA) directs innervation of the developing mouse femur to promote vascularization and osteoprogenitor lineage progression. At the start of primary ossification, TrkA-positive axons were observed at perichondrial bone surfaces, coincident with NGF expression in cells adjacent to centers of incipient ossification. Inactivation of TrkA signaling during embryogenesis in TrkAF592A mice impaired innervation, delayed vascular invasion of the primary and secondary ossification centers, decreased numbers of Osx-expressing osteoprogenitors, and decreased femoral length and volume. These same phenotypic abnormalities were observed in mice following tamoxifen-induced disruption of NGF in Col2-expressing perichondrial osteochondral progenitors. We conclude that NGF serves as a skeletal neurotrophin to promote sensory innervation of developing long bones, a process critical for normal primary and secondary ossification.